Cross-education Mechanisms and Clinical Rehabilitation Research: A Literature Review - Sun, Liang; Wang, Yi; Luo, Lanfang; Yang, Yi; Luo, Jiong (Quality in Sport, 2024)
In recent years, cross-education has garnered significant attention in the fields of clinical rehabilitation and sports training. Since the discovery of CE, a growing number of studies have focused on understanding its characteristics for deeper insight and application. Two theoretical models currently attempt to explain this adaptive mechanism and are mutually compatible: the "cross-activation" model, which suggests that adaptations to unilateral exercise extend to the contralateral side of the body, and the "bilateral-access" model, which posits that the motor patterns of unilateral activities are replicated on the opposite side.When formulating clinical rehabilitation prescriptions, factors such as the patient’s gender and training experience must be considered. Males and inexperienced patients seem to benefit more significantly. High-intensity eccentric unilateral resistance training is recommended for rehabilitation exercises, ideally over a period exceeding four weeks with intervals of 1-2 days between sessions. Each intervention should include 2-3 minutes of rest between sets to allow sufficient recovery time, thereby preventing neuromuscular fatigue and enhancing the benefits of CE, ultimately promoting and accelerating the rehabilitation process.